The machines of evolution and the scope of meaning - Tomlinson, Gary (Zone Books, 2023)
"Merging recent evolutionary thought, theories of information and signs, and new findings in animal studies, Gary Tomlinson's The Machines of Evolution and the Scope of Meaning offers a groundbreaking account of meaning in our world"--